Ingestion of a denture cleanser: Did it cause gastric perforation? - Ingram, Daniel M. (Springer-Verlag, 2008)
INTRODUCTION: Human ingestion of denture cleansers leading to gastric perforation has not previously been described. CASE REPORT: A 27-year-old male ingested three denture cleanser tablets in water over two days in an attempt to cause a false-negative result on a workplace urine drug screen. Seven days later he presented to an emergency department with a perforated gastric ulcer. DISCUSSION: A literature review of cases and the chemistry of the components of his ingestion was conducted to determine the possible relationship between these events. Ingestion of intact fragments of the tablets would be likely to result in significant gastric toxicity, but ingestion of dissolved tablets would be unlikely to have caused his illness.